MITIGASI PEMBIAYAAN BERMASALAH PADA BMT UGT SIDOGIRI CABANG LARANGAN SIDOARJO - Mawardi, Imam (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
Abstract This research has problematic financing implemented by Baitul Mal Wa Tamwil, so early prevention in financing can be effective and efficient. The positive impact operated by the Baitul Mal Wa Tamwil Institute in the welfare of the community and especially for small communities. This research method is descriptive qualitative. Data analysis techniques, namely from field studies and literature studies. The results of the research are to quantify problematic financing, it is carried out with preventive, detective, and curative mechanisms, there is problematic financing because the cause is an error on the part of the BMT Institution, then a lack of accuracy to conduct a survey in analyzing financing. There are other factors in the business that have been practiced by members due to factors from outside the BMT UGT Sidogiri Institute. The implementation in this research is that the financing supervision strategy implemented in the form of preventive, detective, and curative stages at the BMT UGT Sidogiri Sidoarjo Branch is effective enough to reduce problematic financing. Keywords: Mitigation, Problematic Financing, BMT UGT Sidogiri Sidoarjo Branch